Математические модели асинхронного электропривода с векторным управлением для задач оптимизации полиномиальным методом с использованием диаграмм качества управления - Литвиненко, Д.Г. (Електротехніка і електромеханіка, 2011)
The article considers mathematical models of a vectorcontrolled asynchronous electric drive for solving astatic speed regulator synthesis problems by a polynomial equations method and for parameter optimization with a complex criterion of maximum quality and stability factors for the drive dynamic characteristics improvement.